2005
DOI: 10.1016/j.cardiores.2005.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active HIF-1α improves perfusion and arterial remodeling in an endovascular model of limb ischemia

Abstract: In a model that resembles atherosclerotic obstruction of peripheral arteries in patients, the i.m. administration of AdCA5 promoted arteriogenic and angiogenic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 30 publications
6
114
0
1
Order By: Relevance
“…To overcome these technical limitations, we treated BMDACs with DMOG ex vivo to induce HIF-1␣ and HIF-2␣ without exposure of cells to a recombinant vector and to avoid the potential blunting of homing signals from the ischemic limb that might occur with systemic DMOG treatment. Because dose scaling is an important problem in terms of translation to clinical studies, we used the lowest AdCA5 dose with positive angiogenic effects as described in previous studies (4,12,17). We also injected a smaller number of BMDACs (5 ϫ 10 5 cells).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome these technical limitations, we treated BMDACs with DMOG ex vivo to induce HIF-1␣ and HIF-2␣ without exposure of cells to a recombinant vector and to avoid the potential blunting of homing signals from the ischemic limb that might occur with systemic DMOG treatment. Because dose scaling is an important problem in terms of translation to clinical studies, we used the lowest AdCA5 dose with positive angiogenic effects as described in previous studies (4,12,17). We also injected a smaller number of BMDACs (5 ϫ 10 5 cells).…”
Section: Discussionmentioning
confidence: 99%
“…IM AdCA5 injection was previously shown to induce VEGF and PLGF expression in ischemic muscle (4,17). Because VEGFR1/VEGFR2 surface expression was observed in the majority of BMDACs, we studied whether AdCA5 injection increased BMDAC homing after IV injection of vehicle-or DMOG-treated cells.…”
Section: Molecular Characterization Of Dmog-treated Bmdacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia results in loss of prolyl hydroxylation of HIF-1α and a consequent reduction both in the level of HIF-1α ubiquitination and in its de g radation by the proteasome, leading to increase in HIF-1α abundance and HIF-mediated transcriptional responses 34 . Some studies indicate that constitutively active HIF-1α or inhibition of HIF-1α inactivation induces angiogenesis and causes differences in HIF-1α expression between ischemic groups 14,35,36 . Whereas there is no procedure for inhibition of HIF-1α degradation in our study, we found no difference in HIF-1α expression between ischemic groups.…”
Section: Discussionmentioning
confidence: 99%
“…7 The transcription factor, hypoxia-inducible factor-1α (HIF-1α), contains the VEGF gene promoter (ie, the hypoxia-responsive element), and thereby enhances the transcription of VEGF under hypoxic conditions. 8 In addition, it is worth noting that the local overexpression of HIF-1α by viral vector enhanced angiogenesis in the absence of ischemia, 9 and that in addition to VEGF production, activation of HIF-1α upregulated various proangiogenic chemokines, including basic fibroblast growth factor, angiopoietin-1, and SDF-1α. 5, 10 Overall, HIF-1α is essential for hypoxia-mediated proangiogenic signaling.…”
Section: Article P 986mentioning
confidence: 99%